The Influence of the Coaches’ Demographics on Young Swimmers’ Performance and Technical Determinants - Marinho, Daniel A.; Barbosa, Tiago M.; Lopes, Vitor P.; Forte, Pedro; Toubekis, Argyris G.; Morais, Jorge E. (Frontiers in Psychology, 2020)
The purpose of this study was to understand the relationship between the coaches’ demographics (academic degree, and/or coaching level, and/or coaching experience) and young swimmers’ performance and technical ability. The sample was composed by 151 young swimmers (75 boys and 76 girls: 13.02±1.19 years-old; 49.97±8.77 kg of body mass; 1.60±0.08 m of height; 1.66±0.09 m of arm span), from seven different clubs. Seven coaches (one per club) were responsible for the training monitoring. Performance and a set of biomechanical variables related to swim technique and efficiency were assessed. The swimmers’ performance was enhanced according to the increase in the coaches’ academic degree (1: 75.51±10.02 s; 2: 74.55±9.56 s; 3: 73.62±7.64 s), coaching level (1: 76.79±11.27 s; 2: 75.06±9.31 s; 3: 73.65±8.43 s), and training experience (≤ 5 training experience: 75.44±9.57 s; > 5 training experience: 74.60±9.54 s). Hierarchical linear modelling retained all coaches’ demographics characteristics as main predictors (being the academic degree the highest: estimate = -1.51, 95CI: -0.94;-2.08, p = 0.014). Hence, it seems that an increase in the demographics of the coaches appears to provide them with a training perspective more directed to the efficiency of swimming. This also led to a higher performance enhancement.